2020
DOI: 10.1039/c9nr09148c
|View full text |Cite|
|
Sign up to set email alerts
|

A robust Mn@FeNi-S/graphene oxide nanocomposite as a high-efficiency catalyst for the non-enzymatic electrochemical detection of hydrogen peroxide

Abstract: Synthesis procedure of a Mn@FeNi-S/GO nanocomposite and its characterization and electrocatalytic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 45 publications
3
26
0
1
Order By: Relevance
“…To further confirm the Dy 2 Sn 2 O 7 /GO composite, FTIR was investigated, and the results are shown in Figure C. The FTIR spectrum of GO displayed the main characteristic peaks at 3401, 1398, and 1062 cm –1 corresponding to the hydroxyl stretching vibrations of C–OH, deformation of OH to C–OH, and stretching vibrations of C–O . Furthermore, the Dy 2 Sn 2 O 7 NPs showed two clear peaks, at 529 and 469 cm –1 , due to the stretching vibrations of metal–oxygen bonds .…”
Section: Resultsmentioning
confidence: 99%
“…To further confirm the Dy 2 Sn 2 O 7 /GO composite, FTIR was investigated, and the results are shown in Figure C. The FTIR spectrum of GO displayed the main characteristic peaks at 3401, 1398, and 1062 cm –1 corresponding to the hydroxyl stretching vibrations of C–OH, deformation of OH to C–OH, and stretching vibrations of C–O . Furthermore, the Dy 2 Sn 2 O 7 NPs showed two clear peaks, at 529 and 469 cm –1 , due to the stretching vibrations of metal–oxygen bonds .…”
Section: Resultsmentioning
confidence: 99%
“…Based on the proposed mechanism, the electroreduction of H 2 O 2 was carried out in two steps: (i) the adsorption of H 2 O 2 on the surface of the electrode and (ii) the reduction of H 2 O 2 to OH − by electrons on the surface of the g-C 3 N 4 /MWO 4 heterojunction. 56–58 The samples with enhanced absorption features and an excellent electron transfer performance are favored for H 2 O 2 reduction. Between the different MWO 4 , (M = Cu) CuWO 4 showed the lowest bandgap.…”
Section: Resultsmentioning
confidence: 99%
“…As a novel two-dimensional nanomaterial, graphene oxide (GO) has become a promising candidate in constructing biosensors and carrying metal nanomaterials owing to its large surface area, abundant functional groups, excellent conductivity, high hydrophilicity as well as outstanding mechanical stiffness [ 20 , 21 ]. Studies have demonstrated that employing GO to modify electrode surfaces could effectively optimize the electrical response signal of chloramphenicol [ 22 ], ractopamine, clenbuterol [ 23 ], hydrogen peroxide [ 24 ], hydrazine [ 25 ], and so forth [ 26 ]. Diverse compatible materials (e.g., ZnO [ 27 ], TiO 2 [ 28 ], CuO [ 29 ], Co 2 SiO 4 nanobelts [ 30 ]) have been exploited to pair with GO in the fabrication of electrochemical sensors to make full use of their outstanding properties.…”
Section: Introductionmentioning
confidence: 99%